Pembuatan Gelatin dari Tulang Ikan Nila (Oreochromis niloticus) Menggunakan Metode Asam untuk Pengental Sirup Nanas - Wardhana, Krisna Wisnu; Sugiharto, Agung (Talenta Publisher (Universitas Sumatera Utara), 2022)
Imports of gelatin in Indonesia have increased according to demand. Gelatin is a protein derivative from collagen fibers derived from bone extraction. Gelatin contains protein, water and minerals. Gelatin is used to thicken, concentrate, and stabilize fluids such as water, acetic acid, and alcohol. The raw material used in the study was tilapia bone due to the lack of utilization of tilapia bone waste treatment. The purpose of this study was to examine the effect of sulfuric acid concentration on gelatin yield and to apply gelatin as a thickener for pineapple syrup. The methods are degreasing, extraction, and application of pineapple syrup. Variations in the concentration of H2SO4 were 1%, 3%, 5%, and variations in immersion time were 10 hours, 24 hours, and 36 hours. The analysis carried out on tilapia bone gelatin consisted of yield, acidity (pH) and viscosity. The best yield was produced using 1% H2SO4 and 10 hours immersion, which was 13.77%. The largest pH was produced at 2.47 with the use of 5% H2SO4 and immersion for 24 hours, and the largest viscosity was produced at 7.66 cP with the use of 5% H2SO4 and immersion for 36 hours.